High Spin Hall Conductivity in Large‐Area Type‐II Dirac Semimetal PtTe2 - Xu, Hongjun; Wei, Jinwu; Zhou, Hengan; Feng, Jiafeng; Xu, Teng; Du, Haifeng; He, Congli; Huang, Yuan; Zhang, Junwei; Liu, Yizhou; Wu, Han‐Chun; Guo, Chenyang; et al. (Advanced materials (Weinheim), 2020)
Manipulation of magnetization by electric‐current‐induced spin–orbit torque (SOT) is of great importance for spintronic applications because of its merits in energy‐efficient and high‐speed operation. An ideal material for SOT applications should possess high charge‐spin conversion efficiency and high electrical conductivity. Recently, transition metal dichalcogenides (TMDs) emerge as intriguing platforms for SOT study because of their controllability in spin–orbit coupling, conductivity, and energy band topology. Although TMDs show great potentials in SOT applications, the present study is restricted to the mechanically exfoliated samples with small sizes and relatively low conductivities. Here, a manufacturable recipe is developed to fabricate large‐area thin films of PtTe2, a type‐II Dirac semimetal, to study their capability of generating SOT. Large SOT efficiency together with high conductivity results in a giant spin Hall conductivity of PtTe2 thin films, which is the largest value among the presently reported TMDs. It is further demonstrated that the SOT from PtTe2 layer can switch a perpendicularly magnetized CoTb layer efficiently. This work paves the way for employing PtTe2‐like TMDs for wafer‐scale spintronic device applications. PtTe2, a layered type‐II Dirac semimetal, is successfully synthesized in a scalable and controllable manner. High spin–orbit torque and large spin Hall conductivity are found in these PtTe2 thin films, which manifest the potential of PtTe2 thin film for energy‐efficient magnetization switching. The experiments establish a primary basis for further research on similar systems for high‐performance spintronic devices.